DNA‐Mediated Self‐Assembly of Plasmonic Antennas with a Single Quantum Dot in the Hot Spot. Issue 26 (8th February 2019) - Nicoli, Francesca; Zhang, Tao; Hübner, Kristina; Jin, Boyuan; Selbach, Florian; Acuna, Guillermo; Argyropoulos, Christos; Liedl, Tim; Pilo‐Pais, Mauricio
Abstract: DNA self‐assembly is a powerful tool to arrange optically active components with high accuracy in a large parallel manner. A facile approach to assemble plasmonic antennas consisting of two metallic nanoparticles (40 nm) with a single colloidal quantum dot positioned at the hot spot is presented here. The design approach is based on DNA complementarity, stoichiometry, and steric hindrance principles. Since no intermediate molecules other than short DNA strands are required, the structures possess a very small gap (≈ 5 nm) which is desired to achieve high Purcell factors and plasmonic enhancement. As a proof‐of‐concept, the fluorescence emission from antennas assembled with both conventional and ultrasmooth spherical gold particles is measured. An increase in fluorescence is obtained, up to ≈30‐fold, compared to quantum dots without antenna. Abstract : Plasmonic antennas with a single quantum dot (QD) located in the gap between two metallic nanoparticles are self‐assembled in solution using DNA complementarity, stoichiometry, and the disproportionate size between the two species (steric‐hindrance). The resulting QD–antennas display a fluorescence emission with enhancement in both, intensity and emission rate.